Implikatur Bahasa dalam Novel Bekisar Merah Karya Ahmad Tohari - Hanisa; Alan (FKIP, Universitas Lakidende Unaaha, 2024)
This study examines conversational implicatures arising from violations of the cooperative principle in the novel Bekisar Merah by Ahmad Tohari. It analyzes and describes the types of conversational implicatures that emerge due to violations of Grice's maxims within the cooperative principle. Theoretically, the findings of this study are expected to contribute to the development of pragmatic studies, particularly in understanding conversational implicatures in modern contexts. Practically, this research aims to provide insights into the use of conversational implicatures in verbal interactions. This study employs a qualitative approach with a descriptive method. The research data consist of character dialogues in the novel, collected through reading and note-taking techniques. The analysis results indicate that Bekisar Merah contains various forms of conversational implicatures resulting from violations of the four cooperative maxims: the maxim of quantity, the maxim of quality, the maxim of relevance, and the maxim of manner. From the analysis of 21 conversational data samples, it was found that violations of these maxims generate various implicatures that enrich the meaning of interactions between characters. This study is expected to serve as a reference for future research and inspire further studies on conversational implicatures, particularly those related to violations of the cooperative principle in literary works.